PENGAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MODEL E-LEARNING PADA MASA PANDEMI COVID-19: TEACHING OF ISLAMIC RELIGIOUS EDUCATION WITH E-LEARNING MODEL DURING THE COVID-19 PANDEMIC - Mohammad Ali Mortadlo; Asriana Kibtiyah (Risalah, Jurnal Pendidikan dan Studi Islam, 2021)
Abstract The COVID-19 pandemic has become a fairly vicious epidemic because it attacks all countries in the world. To anticipate and reduce the spread of the virus, the world of education uses E-Learning as a shortcut to stay safe and reduce the spread of COVID-19. Researchers are interested in knowing PAI learning with the E-Learning model during the COVID-19 emergency at SMP Negeri 1 Ngoro. There are 3 focuses in this research, namely. 1) Implementation of the E-Learning teaching model in PII subjects, 2) PAI teacher innovation in E-Learning learning, 3) Supporting and inhibiting factors of PAI learning in the E-Learning model. This type of research is qualitative research. With a qualitative approach, explanation aims to develop PAI teaching theory and explain changes in phenomena that occur with the influence of influencing factors. From the results of the study, it can be seen that: first, SMP Negeri 1 Ngoro applies an E-Learning learning model, namely the Learning Management System (LMS) which uses a google suite account facility in which there is a google classroom application that functions as a medium for sending and assessing assignments as well as interactions in class. In cyberspace, the Google Form is used as an assessment tool in the form of questions, both multiple choice and description questions, and WhatsApp as a communication application for learning activities. Second, PAI teachers innovate in PAI learning, including using blended learning by combining online and offline activities and hybrid learning, a combination of Synchronous and Asynchronous. Third, there are several inhibiting factors including: 1) signal interference, 2) not having an ideal device, 3) students who are still clueless and need learning assistance, 4) lack of a sense of independence and responsibility in learning. Supporting factors 1) quota assistance from the government, 2) google suite facilities with unlimited storage systems, 3) school internet area with a capacity of 100 megabytes Keywords: Teaching, Islamic Religious Education, E-Learning Model